2017
DOI: 10.4103/psychiatry.indianjpsychiatry_67_17
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of delirium in alcohol dependence syndrome: Clinical and neurobiological implications

Abstract: Introduction:Alcohol withdrawal delirium (AWD) or delirium tremens (DT) is associated with severe complications and high mortality. Prospectively identifying patients with increased risk of developing DT would have important preventive and therapeutic implications. Thus, the present study aimed to identify clinical risk factors predicting the development of DT.Materials and Methods:The study was a cross-sectional quasi-experimental one with equivalent control group, conducted at a tertiary hospital from August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
10
0
2
Order By: Relevance
“…18 (Ferguson et al (1996)). We found a positive correlation between the severity of alcohol dependence and withdrawal delirium (R = 0.260 and P = 0.000*) -implies that as the severity of dependence increases, the probability of delirium presentation also increases, which is in line with a study by Sarkar et al 14 finding of continuous drinking as a risk factor for delirium. Most of the samples clustered at higher values of SADQ in those presented with delirium.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…18 (Ferguson et al (1996)). We found a positive correlation between the severity of alcohol dependence and withdrawal delirium (R = 0.260 and P = 0.000*) -implies that as the severity of dependence increases, the probability of delirium presentation also increases, which is in line with a study by Sarkar et al 14 finding of continuous drinking as a risk factor for delirium. Most of the samples clustered at higher values of SADQ in those presented with delirium.…”
Section: Discussionsupporting
confidence: 91%
“…12 When compared, the impact of sociodemographic factors between with and without delirium, no significant differences. [14][15][16] found, except gender. Among total of 667 patients, 216 males and 50 females presented with delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our results, Mitchell et al (2017) showed that delirium in hospital had an as-sociation with all-cause one-year mortality following hip fracture in older cases with no dementia (31). Also, similar to previous studies, the other underlying factors can affect mortality rate including cancer (32), hepatic (33), renal (34), and hematologic diseases (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…Интенсивная терапия алкогольного делирия должна проводиться в условиях отделения интенсивной терапии. Ее необходимо начинать незамедлительно, как только диагностирована белая горячка [45]. Основными задачами являются: снижение/устранение возбуждения и других симптомов делирия, диагностика и лечение сопутствующих заболеваний, адекватное, протокольное лечение ААС [18,55].…”
Section: судорогиunclassified